SOCIALIZATION FOR THE IMPLEMENTATION OF E-LEARNING TEACHING MODELS FOR TEACHERS AND EDUCATION STAFFS AT SMA SULTAN AGUNG PEMATANGSIANTAR - Sherly .; Herman .; Fitria Halim; Julyanthry .; Edy Dharma; Ridwin Purba; Rosita Manawari Girsang (LPPM Univ. Ibn Khaldun Bogor, 2021)
This community service had the aim of improving and developing teachers' online teaching learning processes for students. Rapid shifts in different aspects of life are one of the hallmarks of the globalization period. One of them is the advancement of science and technology, especially Information and Communication Technology (ICT), which has a significant positive impact on educational development. Teachers, in particular, need multimedia in the learning process. Educators play a critical role in guiding the learning process in the classroom. Teachers would find it easier to conduct online learning as a result of this socialization. Lectures with presentations, as well as drills or practice, are used in this community service project. After completing the activity, the researchers discovered the following findings: 1) Zoom, Google Classroom, and WhatsApp were chosen to be used by teachers in the teaching learning process; 2) Teachers agreed that e-learning was an important method of learning, 3) The soft skills of teachers in the use of certain e-learning resources improved, and 4) Teachers were willing to agree that the online teaching learning method was a part of teaching learning.